Acoustic demands and influencing factors in facilities for the elderly. (15th December 2020) - Wang, Luying; Kang, Jian
Highlights: Acoustic demands of the elderly examined and effects of six influencing factors. Almost half of the participants chose not to add or abate any sound. The remaining participants required the addition of mainly soothing music. Activity type was an important factor influencing acoustic demands. Women were more likely to demand the addition of natural sounds, relative to men. Abstract: The aim of this study was to examine the characteristics of the elderly individuals' acoustic demands and the effects of six influencing factors, categorized into the following three types: activity type, objective environment (number of people in a room, sound pressure level), and demographic factors (age, sex, and occupation type). In addition, we sought to identify relationships between sound preference and acoustic demands. The study was based on a semi-structured interview survey and objective measurements recorded in six facilities for the elderly in China. The results suggested that almost half of the interviewees chose not to add or abate any sound. For the remaining participants, the addition of mainly soothing music to the environment was required, indicating a considerable preference for it over natural sounds, stimulating music, and other sounds. Activity type was an important factor influencing acoustic demands, in that playing ball games and sitting still tended to engender demands for the addition of sounds, while people who were playing or watching Chinese chess did not wish to hear any sounds including soothing music. An analysis of the number of people in a room showed that if that number reached 12, demands for the abatement of sounds increased sharply, particularly for the sound of people talking. In addition, sound pressure level, age, sex, and occupation type (mental or physical work) influenced the demand for acoustic abatement, which involved the abatement of the sound of people talking or other noises and 'no need to abate'. Natural sounds were seldom required during most activities, with the exception of chatting and sitting still, which is inconsistent with the extent to which people enjoy such sounds. However, there was a significant positive correlation between the elderly individuals' preference for the overall acoustic environment and their demands for the addition of natural sounds. Furthermore, women were more likely to demand the addition of natural sounds, relative to men.